Menyeimbangkan Profit Dan Planet: Environmental Management Accounting Sebagai Strategi Keberlanjutan Perusahaan - Arif Santoso (Jurnal Riset Akuntansi, 2024)
The Product and Textile Industry (TPT) is facing environmental issues due to the environmental impacts it causes. TPT is the main industry in Central Java and since 2022 has shown a significant decline in performance. The purpose of this study is to provide a comprehensive study to address global challenges and the sustainability of the TPT industry business in Central Java. This study is a qualitative study using secondary data. The data were then analyzed using the Miles and Huberman and VOSviewer techniques. The stages of analysis include data reduction, data presentation, and drawing conclusions. This study found that the TPT industry faces two main problems, namely global challenges and business sustainability. This study identifies two global challenges, namely the transition of consumer preferences and environmental issues. The second global challenge poses problems to the profitability and business desirability of firms. The recommendation given for this problem is the application of Environmental Management Accounting (EMA). EMA implementation requires synergy between government, industry, society, and universities. EMA can address global challenges and business sustainability through accelerated accounting, awareness, environmental disclosure, and increased legitimacy. In the end, the implementation of EMA can increase the resilience of the TPT industry amid global challenges and sustainability issues.